2004 Kansas performance tests with spring small grains - Roozeboom, Kraig (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2013)
Kansas performance tests are designed to evaluate small grain varieties in several environments by using recommended production practices. Varieties are evaluated for yield, test weight, maturity, height, and other characters that may arise in a given season.
Keywords: Kansas; Yield; Environmental factors; Oats; Spring wheat; Spring-planted winter wheat; Triticale